Monitoring and evaluating human development indicators (HDI's) in the OECS - Soomer, June (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Focuses on both economic and geographical vulnerabilities and the mitigation response to those things that seem to put us at a disadvantage. Looks at the launching of the OECS Human Development Report, the adoption of the OECS Development Charter and examines the strategies to address economic recovery.